Are there any additional mechanisms for haemolysis in HELLP syndrome?. Issue 142 (June 2016) - Sabau, L.; Terriou, L.; Provot, F.; Fourrier, F.; Roumier, C.; Caron, C.; Susen, S.; Ducloy-Bouthors, A.S.
Abstract: HELLP syndrome is a microangiopathy that leads to severe maternal complications. The objective of this study was to identify any additional mechanisms that could have contributed to HELLP syndrome-induced haemolysis. This is a pilot, prospective and observational study that lasted 9 months. All patients with HELLP syndrome treated at academic tertiary care women hospital accepted to participate. Sixteen patients were included. In ten patients (63%), schizocytes were detected following a blood smear test. Six patients (38%) were diagnosed with a partial expression deficiency of proteins regulating the complement system (CD 55 or CD 59). In nine patients (56%), an activation of the complement classical pathway was detected. In two patients (13%), an ADAMTS 13 activity below 30% was detected. Three patients (19%) were diagnosed with a folate deficiency and one (6%) with an antiphospholipid syndrome. All patients developed maternal or fetal morbidity including nine (56%) an acute kidney injury. All patients but one had at least one additional mechanism that could contribute to haemolysis, besides a simple physical injury. Larger studies should be promoted to understand haemolysis in HELLP syndrome. Highlights: Additional mechanisms of haemolysis are involved in HELLP syndrome. Transient deficiency of proteins regulating complement system and ADAMTS 13 deficiency were the main observed mechanisms. Others mechanisms were vitamin deficiencies and auto immune disease.